STUDENTS’ STRATEGIES IN LEARNING SPEAKING SKILLS AT SMP NASRANI 3 MEDAN - Lingga, Laura Maloni; Simanjuntak, Reka Monika; Sembiring, Yenita (UNDIKMA Mataram (Eks. IKIP Mataram), 2020)
Speaking is one of the speaking skills possessed by students. Speaking skills have been trained from an early age, but the results of speaking learning are still far applied. Many students still experience difficulties in learning to speak. such as shame, fear and anxiety and lack of confidence inhibiting learning factors in speaking to students lacking motivation, poor student learning habits, mastery of students' vocabulary is still low, as for student learning strategies are one aspect that determines the success of students in speaking, students can have student learning strategies by memorizing vocabulary, believing themselves and improving vocabulary pronunciation. This research was conducted to identify the difficulty of speaking in English faced by students and find out the strategies they used to overcome these difficulties. This researcher used a qualitative descriptive method involving as many as 17 students in grade 9 at 3 Medan Christian Middle School, research results this shows that students have difficulty speaking in English namely lack of grammatical understanding, lack of vocabulary, incorrect pronunciation of words fearing the response of others feeling nervous in making mistakes, lack of self-confidence and shame in the strategy that students do is asking help to others trying to compose sentences in different ways by using gestures, taking the rules in positive thinking, can be concluded that students have a sense of difficulty in speaking English.